"It Put Me in a Really Uncomfortable Situation": A Need for Critically Conscious Educators in Interworldview Efforts. Issue 2 (3rd April 2019) - Armstrong, Amanda
Abstract: College students are majoritized and minoritized through micro- and macro-level inequities because of their varied and multiple worldview identities (e.g., [non]religious and spiritual). Ongoing interfaith efforts in higher education prove to be both beneficial, promoting interworldview engagement, and challenging, sometimes further marginalizing religiously minoritized students. In this article, I explore how educators, and their own capacities to support students' worldviews and think, act, and respond in critically conscious ways, influenced how some students experienced worldview inequities at one four-year institution. Findings suggest that institutional efforts for promoting interworldview engagement among students should focus much more on educators' awareness of worldview differences.